AB1079 CHECKPOINT INHIBITOR-ASSOCIATED ARTHRITIS: PHENOTYPES AND CYTOKINE ASSOCIATIONS. (June 2019) - Chan, Karmela Kim; Vitone, Gregory; Shanaj, Sara; Tirpack, Aidan; Finik, Jackie; Donlin, Laura; Rao, Deepak; Benson, Caroline; Bykerk, Vivian; Orange, Dana; Brenner, Michael; Goodman, Susan; et al.
Abstract : Background: Immune checkpoint inhibitors (CI) have revolutionized cancer management, but can also cause immune-related adverse events. Five percent of CI-treated patients develop inflammatory arthritis, but it is poorly defined phenotypically and immunologically. Objectives: To characterize phenotypes of CI-associated arthritis, and compare cytokine levels in these patients to rheumatoid arthritis (RA) and osteoarthritis (OA) controls. Methods: Patients referred for CI-associated arthralgia or arthritis were prospectively enrolled in an institutional registry. Serum was collected when patients underwent phlebotomy for a clinical indication. We used a Luminex Human Magnetic Assay to measure levels of IL-1β, IL-2, IL-6, IL-8, IL-10, IL-12, IL-17, IL-22, TNF, IFN-γ, PD-L1, CCL2, CXCL2, CXCL13, OSM, CCL20, GM-CSF, CXCL-11 in CI-treated patients, and in stored serum from 7 RA patients (matched for medication, age, sex, CDAI) and 4 OA patients (age, sex matched). All comparisons were planned a priori. Results: Thirty-six patients were enrolled 5/1/18-1/25/19. Median [IQR] age was 67[58-78], 18(50%) were female, 14(39%) were smokers and 13(36%) had melanoma. Twenty-two (61%) were on anti-PD1 or PD-L1 monotherapy, and the remainder were on combination CI. Phenotypes included 1. Small joint involvement in 17(47%), 2. Exclusively large joint involvement in 6(17%), 3. Arthralgia without arthritis in 9(25%), and 4. Polymyalgia rheumatica in 4(11%). In all, 7(19%) had concomitant tenosynovitis or enthesitis, mostly accompanying large joint arthritis or arthralgia (6/7). Median CDAI at entry was 11[7-23] and median ESR 29[18-44]. The majority (58%) of patients with the small joint phenotype were RF and/or CCP positive and one had erosive disease, compared to none with the large joint phenotype. ANA positivity was common (74%) and did not vary across phenotypes. Median time of symptom onset was 4[0.8-12] months after CI initiation. Median follow up was 7[3-22] months but only 5(14%) had resolution of arthritis off medication during that period. 22(61%) required CI discontinuation, 5(14%) due to arthritis. 29(81%) required steroids including 15(42%) who required >20mg prednisone. 19(53%) required a synthetic DMARD and 5(14%) required a biologic DMARD. Of 33 patients with known cancer status, 15(45%) had a complete response, 5(15%) a partial response, 5(15%) "stable" disease, 6(18%) progression, and 2(6%) died. Cytokines were measured in 22 patients, who were similar to the cohort as a whole except for more CCP positivity (p=0.02). CI patients with the small joint phenotype had higher levels of IL-6 than RA controls (p=0.04) (Figure 1 ) and IL-6 levels trended higher in the small joint vs. exclusively large joint phenotype (Figure 2 ). The B cell chemoattractant CXCL13, a factor produced by T peripheral helper cells in RA synovium 1, trended higher in the serum of CI patients (Figure 3 ). Other cytokine levels did not differ significantly in patients with the small joint vs. exclusively large joint phenotype, or in CI-arthritis patients vs. controls. Conclusion: Half of patients with CI-arthritis present with an RA-like phenotype with small joint involvement and frequent seropositivity, and have elevated levels of IL-6 compared to RA patients. This small joint phenotype may represent an accelerated form of RA. References: [1] Rao DA, et al. Nature 2017: 542(7639):110-114 Disclosure of Interests: Karmela Kim Chan Grant/research support from: Roche: sponsored research agreement on stromal cells, Consultant for: GSK: consultant. (I am part of their immunology network, a group of about 8 immunologists who advise them regularly and broadly in the areas of inflammation and infection)., Gregory Vitone: None declared, Sara Shanaj: None declared, Aidan Tirpack: None declared, Jackie Finik: None declared, Laura Donlin: None declared, Deepak Rao Grant/research support from: Merck - Sponsored research project funding support, Consultant for: Janssen - Consultant Scipher Medicine - Consultant Amgen - Scientific advisory board Patent submitted on Tph cells, Caroline Benson: None declared, Vivian Bykerk Grant/research support from: Mallinckrodt, BMS, Crescendo Biosciences, Sanofi/Regeneron., Consultant for: Amgen, Pfizer, UCB, Scipher, Sanofi/Genzyme/Regeneron, Dana Orange Consultant for: Astra Zeneca and Pfizer., Michael Brenner Grant/research support from: Roche: sponsored research agreement on stromal cells (but has nothing to do with checkpoint related disease), Consultant for: GSK: consultant. (I am part of their immunology network, a group of about 8 immunologists who advise them regularly and broadly in the areas of inflammation and infection)., Susan Goodman Grant/research support from: Novartis: research support, Consultant for: Novartis, UCB, Pfizer: consulting, Anne Bass: None declared